Płaszczyzny wpływu Kościoła na Solidarność (1980-1981) - Łatka, Rafał (Komunizm: System - Ludzie - Dokumentacja, 2023)
The influence of Catholic Church on the movement Solidarity in Poland it was wide and diversified. Author describe the different perspectives of that influence and divided it on the three main categories. At first it was o common moral rules and the very close view to the political situations and geopolitical issues. Catholic Church had also been trying to affected on the direction of Solidarity agenda and development. At least Episcope had influenced on the particular of social movement leader’s decisions.